Biology and Management of Chinese Privet - Rick Williams; Patrick Minogue (EDIS)
FOR-189, a 3-page illustrated fact sheet by Rick Williams and Patrick Minogue, describes this semi-evergreen to evergreen thick-forming shrub which was introduced as an ornamental shrub in the South in 1852 and is widely naturalized in the Panhandle and northern counties — its biology and management strategies. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.